2020
DOI: 10.1080/03080188.2020.1820154
|View full text |Cite
|
Sign up to set email alerts
|

Ecology-focused aesthetic music education as a foundation of the sustainable development culture

Abstract: Overcoming the current spiritual and ecological crisis plaguing the globe is impossible without changing the paradigm of aesthetic music education. Music should play an important role in achieving the goals of sustainable development, rather than be a utilitarian product of consumer society. Therefore, attention should be drawn to the music teacher education and to a new paradigm of education that is ecology-focused, aesthetic, and enables sustainable development at the urban, suburban, and rural levels. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Some researchers suggest taking into account different types of environments (the specifics of the region; the level of education) and provide music education services within the integrative concept. According to Guo et al (2020), such a study offers the integration model of environmental rationality, aesthetic education and music ecology to build a new educational paradigm. The proposal is based on the five components of society: environmental friendliness, rationality, teachers, sustainable development and music ecology.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers suggest taking into account different types of environments (the specifics of the region; the level of education) and provide music education services within the integrative concept. According to Guo et al (2020), such a study offers the integration model of environmental rationality, aesthetic education and music ecology to build a new educational paradigm. The proposal is based on the five components of society: environmental friendliness, rationality, teachers, sustainable development and music ecology.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, there is a growing field of eco-literacy research in music education (Jorritsma, 2022; Shevock, 2015a, 2015b, 2018, 2020; Shevock & Bates, 2019), which aims to give concrete tools to provide socially and environmentally conscious music education. A contribution to sustainable and ecology-focused development in music education is examined in Varkøy and Rinholm’s (2020) and Guo et al’s (2020) works. Accordingly, many musicians worldwide have focused on increasing awareness of climate change (ClimateKeys, 2019; Climate-Music Project, 2019), and some research on composing and climate change has already been carried out (Galloway, 2020; Johnson, 2017).…”
Section: Climate Change Challenges Music Educators’ Educational Rolementioning
confidence: 99%
“…According to Guo, Su and Yue, the global spiritual and ecological crisis could not be solved without changing the paradigm of music aesthetic education. Contemporary educational methods should be improved by expanding ecological and integrative ways of thinking to elevate the art of music to a new realm with the higher goal of creating sustainable communities of ecologically responsible individuals (Guo;Su;Yue, 2020, p. 564-580). Sabirovna's survey found that modern students, especially teenage students, have a vague understanding of serious classical art.…”
Section: Introductionmentioning
confidence: 99%